In Vitro Evaluation of Sunscreen Activity of Extract and Fraction of Kedabu Fruit (Sonneratia ovata Backer) : Uji Aktivitas Tabir Surya Ekstrak dan Fraksi Buah Kedabu (Sonneratia ovata Backer) Secara In Vitro - Lestari, Putri; Furi, Mustika; Fernando, Armon; Amin, Syahrul; Irfan, Nawwar (Universitas Tadulako, 2025)
The Kedabu fruit, scientifically known as Sonneratia ovata Backer, is a mangrove plant commonly found in Indonesia. This fruit is valued for its antioxidant properties and shows potential as a natural sunscreen. This study was conducted to determine the in-vitro activity of the extract and fractions of Kedabu fruit (Sonneratia ovata Backer) as a sunscreen, with the potential for development into a natural sunscreen preparation. Experiments were conducted on extracts and various fractions, including n-hexane, ethyl acetate, n-butanol, and water. The extracts and fractions of Kedabu fruit were prepared at concentrations of 200, 400, 600, 800, and 1000 µg/mL. Their absorbance was then measured in the UV A (320-375 nm) and UV B (290-320 nm) wavelength ranges. The n-butanol fraction, at a concentration of 1000 µg/mL, appears to be the most effective sunscreen, demonstrating a %Te value of 8.369% and %Tp of 50.345%. This performance places it in the standard Suntan range for UV B protection. Additionally, it has an SPF value of 10.58, categorizing it within the highest level of sun protection.